Efficacy of 2% ibuprofen subgingival irrigation as an adjunct to non-surgical therapy in the treatment of chronic periodontitis: A randomized controlled, split-mouth, clinical trial - Amirhossein Farahmand; Ferena Sayar; Zohreh Omidali; Mahsa Soleimani; Bahareh Jafarzadeh Esfahani (Tabriz University of Medical Sciences, 2019)
Background. Pharmacological factors, such as ibuprofen, released topically in the periodontal pocket modulate the host response and enhance the influence of non-surgical periodontal treatment. Methods. In this double-blind, randomized, split-mouth, clinical trial, 38 outpatients with mild to moderate chronic periodontitis were enrolled by applying the simple random sampling method. They had at least one tooth with a periodontal pocket depth of >4 mm in each quadrant and had undergone phase I of periodontal treatment one week after scaling and root planing (SRP). The parameters of clinical periodontal evaluation, including probing pocket depth (PPD), clinical attachment level (CAL), plaque index (PI), and bleeding index (BI), were measured. In addition, two mandibular molar teeth in one quadrant were randomly nominated for subgingival irrigation with 0.5 mL of 2% ibuprofen or placebo mouthwash. The measurements were repeated after at least one week for three months. Results. Thirty-four individuals (18 women and 16 men), with an age range of 28‒36 years, were evaluated for three months. Moreover, periodontal clinical parameters were assessed within three months. There was a significant improvement in pocket depth (PD) and clinical attachment level (CAL) readings after 12 weeks in both groups (paired t-test). On comparing, the group with scaling and root planing (SRP) + ibuprofen showed more favorable results than the group with SRP + placebo (P<0.05). There were significant improvements in PI and BI in both groups; the differences between the two groups were significant (P<0.05). Conclusion. The mouthwashes containing ibuprofen might reduce the symptoms of periodontal disease and might be used as an adjunct in the healing process